Dwarf planet (1) Ceres surface bluing due to high porosity resulting from sublimation - Stefan E. Schröder (Nature Portfolio, 2021)
The origin of blue ejecta around the fresh craters of dwarf planet Ceres is unknown. Here, the authors show that the blue color results from high porosity of the surface, induced by sublimation of ice-phyllosilicate mixture produced by impacts.